Praktik Budidaya Ubi Kayu di Kecamatan Kulim Kota Pekanbaru - Wani Angelia Purba; Yulia Andriani; Meki Herlon (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2026)
Cassava (Manihot utilissima) is an important food commodity that plays a strategic role in supporting food security and farmers’ livelihoods. Kulim Subdistrict is the largest cassava production center in Pekanbaru City; therefore, the cultivation practices employed by farmers need to be studied to gain a technical understanding of the cultivation methods used in the field. This study aims to describe the cassava cultivation practices implemented by farmers in Kulim Subdistrict, Pekanbaru City. The study employed a qualitative descriptive method, with data collected through observation, interviews, and documentation. The study sample consisted of agricultural extension workers and farmer group leaders who cultivate cassava in Kulim Subdistrict. The results showed that farmers used the “Kelenteng” cassava variety with a 9-month growth period. Land preparation was carried out using a plow and a rotary tiller, while planting was done at a depth of 3–5 cm with a planting spacing of 100 × 100 cm using a square planting pattern and an angled cutting position. Fertilization used a combination of organic and inorganic fertilizers, namely dolomite, manure, urea, NPK Phonska, and KCl. Crop maintenance included thinning at 20–30 days after planting and chemical weed control using Gramoxone and Roundup, while ridging and fungal disease control were not performed. Harvesting is carried out 9–10 months after planting, done manually, with yields ranging from 13 to 14 metric tons per hectare. Cassava cultivation practices in Kulim Subdistrict are still largely based on farmers’ experience and knowledge, which help support cassava farm productivity.